MEMBANGUN POLITIK HUKUM PEMILU YANG DEMOKRATIS DENGAN MEMBUMIKAN KONSEP NEGARA HUKUM PANCASILA - Ganda Surya Satya Johni Arifin Putra (Faculty of Law, Universitas Diponegoro, 2014)
The Constitutional Court is the guardian and the guardian institution the constitution as the supreme law, but also the guardian of Pancasila as the state ideology bodyguard. Constitutional Court decisions are not only based on certain legal aspects but always consider all aspects of life and the interests of the entire case PHPU.Decisions by way of exemption types, ways of thinking, principles and theories that have been used, the liberation of the culture of law enforcement dominant and is seen hampering efforts to seek justice, thus to view the law is always in the process of being, sensitive to changes in society at local, national, global